Yak hair bionic human hair material based on tannic acid crosslinking modification and preparation method

By pre-treating and coating yak hair through tannic acid cross-linking modification, the problems of gloss, toughness and wearing comfort of wig materials are solved, and the production of highly realistic and environmentally friendly wig materials is achieved.

CN120683711APending Publication Date: 2025-09-23ZHEJIANG GONGSHANG UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510752689.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-06
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing wig materials, especially artificial chemical fibers and untreated yak hair, have problems such as unnatural luster, hard texture, poor air permeability, easy generation of static electricity, and insufficient mechanical strength, which make it difficult to meet the market demand for high simulation and wearing comfort.

Method used

The yak hair was pretreated, swelled with solvent, coated with tannic acid and dried and straightened by tannic acid cross-linking modification to form a dense organic coating, thereby improving the smoothness, toughness and antistatic properties of the fiber.

Benefits of technology

The smoothness and softness of yak hair fiber are improved, and its mechanical strength and antistatic properties are enhanced, making it closer to the appearance and touch of real human hair. It is environmentally friendly and pollution-free, and is suitable for the production of high-quality wig materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120683711A_ABST
    Figure CN120683711A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of textile fiber material modification and wig manufacturing, and discloses a yak hair bionic human hair material based on tannic acid cross-linking modification and a preparation method thereof.The preparation method comprises the following steps that raw material pretreatment is conducted, specifically, healthy and stain-free yak hair raw materials are selected, preferably, fine and soft hair of the yak abdomen is selected, and the raw materials are pretreated; the method comprises the following steps: cleaning and degreasing to remove surface grease and impurities, rinsing with a warm water solution of a nonionic surfactant, fully rinsing with clear water, naturally airing or drying at low temperature, and bleaching as required to remove natural pigments, thereby obtaining the clean light-colored hair raw material. Through hexafluoroisopropanol pretreatment, keratin scale structures on the surfaces of yak hair fibers are swelled and recombined, and original rough scales which are loosely arranged and have a small stacking number become flat and ordered. A layer of flexible and uniform organic thin film is further formed on the surface of the fiber through the subsequent tannic acid cross-linking coating step, and the original rough texture of the yak hair is thoroughly changed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile fiber material modification and wig manufacturing, and in particular to a tannic acid-crosslinked modified yak hair biomimetic human hair material and a preparation method thereof. Background Art

[0002] With people's pursuit of beauty and increasing awareness of hair health, the demand for wigs is growing. Existing wig materials are mainly divided into two categories: one is human hair, which has the advantages of natural texture, high flexibility, and realistic wearing effect. However, the supply of human hair is limited, making it difficult to meet market demand, and it is expensive, resulting in a chronic supply shortage. The other is artificial chemical fibers such as nylon, polyester, and polypropylene. Wigs made from these materials are low-cost and easy to mass-produce, but they have many obvious drawbacks, such as an unnatural sheen that can appear too bright and plastic in sunlight, a hard texture, poor breathability, and a high tendency to generate static electricity, which causes hair strands to stick together and tangle, greatly affecting the wig's lifespan and wearing comfort.

[0003] Against this backdrop, animal hair, a common keratin fiber like human hair, has gradually attracted attention as a potential alternative to wig materials. Yak hair, a byproduct of plateau yaks, offers the advantages of abundant availability and affordability, and shares similarities in chemical composition and molecular structure with human hair. The fine, soft hair found on the yak's abdomen, in particular, lacks melanin. Raman spectroscopy analysis reveals a high degree of similarity in molecular structure to human hair, theoretically making yak hair a promising alternative to human hair. However, there are still obvious shortcomings when using natural yak hair without any treatment as a raw material for wigs: first, yak hair fibers are coarse and hard, and the hair scales on the keratin surface are highly keratinized and loosely arranged, with a small number of scales stacked, resulting in a rough fiber surface and a stiff feel; second, yak hair has a high degree of porosity inside, including voids in the medulla of the hair core, which makes its density low but its strength and toughness are inferior to those of human hair. Macroscopically, its Young's modulus and tensile strength are lower than those of human hair, and the fibers are easily brittle and difficult to withstand mechanical stress such as repeated combing, which seriously limits its effectiveness as a substitute for real hair; in addition, yak hair that has not been specially treated lacks the smooth touch and softness of real hair, and its appearance is difficult to compare with real hair.

[0004] To address these issues, some research has explored modifying animal hair fibers, such as wool and other animal hair, through oxidation, enzyme treatment, or resin coating to improve hand feel and anti-felting properties. However, these traditional methods often have drawbacks, including reduced fiber strength after treatment, environmental pollution from chemical chlorine oxidants, and the inability to fully impart the fibers with the comprehensive properties of human hair, such as gloss, toughness, hydrophilicity, and antistatic properties. Currently, no mature and comprehensive solution exists to effectively overcome the shortcomings of existing wig materials in terms of fidelity, toughness, and stability.

[0005] To this end, those skilled in the art have proposed a yak hair bionic human hair material based on tannic acid cross-linking modification and a preparation method to solve the above problems. Summary of the Invention

[0006] In view of the shortcomings of the existing technology, the present invention provides a yak hair biomimetic human hair material based on tannic acid cross-linking modification and a preparation method, which solves the problems raised in the above background technology.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: a method for preparing a yak hair biomimetic human hair material based on tannic acid cross-linking modification, comprising the following steps:

[0008] Raw material pretreatment: Select healthy, stain-free yak hair, preferably the fine, soft hair from the yak's abdomen. Wash and degrease the hair to remove surface grease and impurities. Immerse the hair in a warm, non-ionic surfactant solution, rinse thoroughly with clean water, air dry or dry at low temperature. Bleaching is performed as needed to remove natural pigments and obtain clean, light-colored hair.

[0009] Solvent swelling treatment: Immerse the pre-treated dry yak hair in hexafluoroisopropanol solvent for 0.5 to 2 hours at room temperature to allow the keratin scale structure on the fiber surface to swell and reorganize moderately, breaking some of the hydrogen bonds between keratin molecules, making the scale layer soft and rearranged. Take out the fiber and gently spin dry.

[0010] Tannic acid cross-linking coating: soak the wet yak hair after HFIP treatment in a 1% to 5% tannic acid aqueous solution at room temperature for 0.5 to 2 hours. A small amount of ethanol can be added to the solution to improve permeability. Slowly shake or stir the solution during this period, and keep the solution at 40 to 60°C for gentle heating to promote the cross-linking reaction between tannic acid and keratin, forming a dense organic coating on the fiber surface. Then remove the fiber, rinse the unreacted tannic acid on the surface with clean water, and gently squeeze out the excess water.

[0011] Drying, straightening and shaping: The wet fibers are straightened and hung on a stainless steel wire mesh rack or stretched on a frame. They are dried at 50-80°C for 1-2 hours until the fibers are completely dry and shaped. If necessary, the dried fibers are lightly finished to obtain yak hair bionic human hair materials with simulated human hair properties.

[0012] Preferably, in the pretreatment step, the concentration of the nonionic surfactant during cleaning and degreasing of the yak hair raw material is 0.1% to 0.5%, the temperature of the warm water solution is 30°C to 50°C, the immersion time is 10 to 30 minutes, the rinsing times are not less than 3 times, and the low-temperature drying temperature does not exceed 60°C.

[0013] Preferably, the bleaching treatment is to place the yak hair in a hydrogen peroxide solution with a mass fraction of 3% to 8%, soak it at room temperature for 2 to 6 hours, then wash it with clean water and an acidic aqueous solution in sequence, the pH value of the acidic aqueous solution is 3 to 5, the soaking time is 5 to 15 minutes, and then wash and dry it.

[0014] Preferably, in the solvent swelling treatment step, the purity of the HFIP solvent is not less than 98%, and the treatment time is 1 to 1.5 hours.

[0015] Preferably, in the tannic acid cross-linking coating step, tannic acid is a natural polyphenol compound extracted from plants, the concentration of the tannic acid aqueous solution is 2% to 3%, the amount of ethanol added is 1% to 3% of the mass of the tannic acid aqueous solution, the soaking time is 1 to 1.5 hours, and the solution heating temperature is 45°C to 55°C.

[0016] Preferably, in the drying, straightening and shaping step, the drying temperature is 60°C to 70°C, the drying time is 1.5 to 2 hours, and the post-finishing includes applying a small tension of 0.1 to 0.3 times the fiber's own weight to straighten the fiber, and using a combing tool to comb the fiber 3 to 5 times at a frequency of 50 to 100 times per minute.

[0017] A bionic human hair material based on tannic acid cross-linked modified yak hair is disclosed. The bionic human hair material is composed of modified yak hair fibers and is similar in appearance and performance to natural human hair. The fiber surface is smooth and soft, exhibiting a silky luster, and has high toughness, elasticity, and tensile strength. The Young's modulus is comparable to that of human hair, the hydrophilicity is improved, and the moisture regain is significantly increased compared to unmodified fibers. The material exhibits excellent antistatic properties and is not easy to knot or tangle.

[0018] Preferably, the modified yak hair fiber has an average diameter of 50 to 100 microns, a tensile strength at break of ≥300 MPa, a Young's modulus ≥5 GPa, a moisture regain ≥12%, and a surface roughness ≤0.5 μm.

[0019] The present invention provides a tannic acid-crosslinked modified yak hair biomimetic human hair material and its preparation method. It has the following beneficial effects:

[0020] 1. Through hexafluoroisopropanol pretreatment, the keratin scale structure on the surface of yak hair fibers swells and restructures, transforming the originally rough, loosely arranged, and thinly stacked scales into smooth, orderly layers. The subsequent tannic acid cross-linking coating step further forms a flexible and uniform organic film on the fiber surface, completely transforming the original rough texture of yak hair. The modified fiber surface is smooth and delicate, exhibiting a natural, soft, silky sheen, unlike the harsh, plastic-like sheen of ordinary synthetic fibers, and more similar to the sheen of high-quality human hair. The texture is soft, non-itchy, and as smooth as human hair, significantly enhancing the realism and aesthetics of wigs and other products when worn, meeting the stringent requirements for hair appearance and feel in wig manufacturing and other fields.

[0021] Second, the present invention forms a durable coating on the fiber surface and internal pores through a cross-linking reaction between tannic acid molecules and keratin. This effectively fills the excess pore space within the yak hair, making the originally fragile and easily broken fiber structure denser and stronger. This allows it to withstand the mechanical stresses of combing and styling during daily wear, making it less susceptible to breakage. This significantly expands its application in wig manufacturing and other fields, effectively addressing the insufficient mechanical properties of traditional wig materials.

[0022] 3. The tannic acid used in this invention is derived from plant extracts and is non-toxic, biodegradable, and environmentally friendly. The hexafluoroisopropanol solvent is also recyclable and reusable, reducing chemical consumption and emissions. Compared to the environmental pollution issues that synthetic wigs can cause during production and disposal, the bionic human hair material provided by this invention achieves high performance while minimizing the environmental burden, embodying the concept of green and sustainable development and offering significant environmental value and cost-effectiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a general flow chart of the preparation method of the present invention;

[0024] Figure 2 This is a flow chart of the tannic acid cross-linking coating steps of the present invention;

[0025] Figure 3 This is a flow chart of the application of the bionic human hair material of the present invention. DETAILED DESCRIPTION

[0026] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the present specification. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0027] Please see the attached Figure 1 -Attached Figure 3 The embodiment of the present invention provides a method for preparing a yak hair bionic human hair material based on tannic acid cross-linking modification.

[0028] Example 1

[0029] Preparation method: operate according to the specific steps in the above-mentioned patent technical solution, and all parameters take the intermediate value, that is, the non-ionic surfactant concentration is 0.3%, the warm water temperature is 40°C, the immersion time is 20 minutes, the rinsing is 3 times, and the low-temperature drying temperature is 50°C; during the bleaching treatment, the hydrogen peroxide solution concentration is 5%, and the fiber is immersed at room temperature for 4 hours, and the acidic aqueous solution has a pH value of 4 and is immersed for 10 minutes; the solvent swelling treatment is treated with a 99% pure HFIP solvent for 1.25 hours; the tannic acid aqueous solution concentration is 2.5%, the ethanol addition amount is 2% of the mass of the tannic acid aqueous solution, and the fiber is immersed for 1.25 hours, and the solution heating temperature is 50°C; the drying temperature for drying, straightening and shaping is 65°C, the drying time is 1.75 hours, and the post-finishing is straightened by applying a small tension of 0.2 times the fiber's own weight, and combing is done 4 times at a frequency of 75 times per minute.

[0030] Performance test results: The modified yak hair fiber has an average diameter of 75 microns, a tensile breaking strength of 320 MPa, a Young's modulus of 5.5 GPa, a moisture regain of 13%, a surface roughness of 0.3 μm, a natural and soft appearance, good flexibility, improved hydrophilicity, excellent antistatic properties, and is not easy to knot or tangle.

[0031] Example 2

[0032] Preparation method: Compared with Example 1, in the tannic acid cross-linking coating step, the concentration of the tannic acid aqueous solution is 1%, and the parameters of other steps are the same.

[0033] Performance test results: The modified yak hair fiber had an average diameter of 72 microns, a tensile strength at break of 305 MPa, a Young's modulus of 5.2 GPa, a moisture regain of 12.5%, and a surface roughness of 0.35 μm. Its gloss and softness were slightly inferior to those of Example 1, but still within acceptable limits. Its hydrophilicity and antistatic properties declined slightly, but were still superior to those of unmodified yak hair and common synthetic fiber wig materials.

[0034] Example 3

[0035] Preparation method: In the solvent swelling treatment step, the treatment time was shortened to 0.5 hours, and other parameters remained the same as in Example 1.

[0036] Performance test results: The modified yak hair fibers had an average diameter of 70 microns, a tensile strength at break of 290 MPa, a Young's modulus of 5.0 GPa, a moisture regain of 12%, and a surface roughness of 0.4 μm. Due to insufficient swelling time, the keratin scale structure was poorly restructured, resulting in suboptimal subsequent tannic acid cross-linking. The fiber's performance indicators were somewhat lower than those of Example 1. However, compared to Example 2, its strength and toughness were slightly lower, and its gloss and flexibility were also slightly inferior.

[0037] Example 4

[0038] Preparation method: The drying time in the drying, straightening and shaping step is extended to 2 hours, and the drying temperature is increased to 70° C. The other step parameters are the same as those in Example 1.

[0039] Performance test results showed that the modified yak hair fibers had an average diameter of 78 microns, a tensile strength at break of 315 MPa, a Young's modulus of 5.4 GPa, a moisture regain of 12.8%, and a surface roughness of 0.32 μm. Prolonging the drying time and increasing the temperature helped the fibers better set and slightly increased their diameter. The performance indicators were comparable to those of Example 1, and the appearance and feel were also similar. However, the moisture regain was slightly lower than that of Example 1, and the hydrophilicity was slightly weakened.

[0040] Example 5

[0041] Preparation method: In the tannic acid cross-linking coating step, the amount of ethanol added was increased to 3% of the mass of the tannic acid aqueous solution, and other parameters were consistent with those in Example 1.

[0042] Performance test results showed that the modified yak hair fibers had an average diameter of 76 microns, a tensile strength at break of 318 MPa, a Young's modulus of 5.3 GPa, a moisture regain of 13.2%, and a surface roughness of 0.28 μm. Increasing the amount of ethanol facilitated better penetration of tannic acid into the fibers, resulting in a more complete cross-linking reaction and a denser coating. This improved the tensile strength and moisture regain of the fibers, reduced surface roughness, and further enhanced gloss and compliance, resulting in overall performance superior to that of Example 1.

[0043] Comparative Example 1 (no tannic acid cross-linking treatment)

[0044] Preparation method: only raw material pretreatment, solvent swelling treatment and drying, straightening and shaping steps are performed on yak hair, and the tannic acid cross-linking coating step is omitted.

[0045] Performance test results showed that the modified yak hair fibers had an average diameter of 73 microns, a tensile strength at break of 250 MPa, a Young's modulus of 4.5 GPa, a moisture regain of 10%, and a surface roughness of 0.6 μm. Without tannic acid cross-linking and coating, the fiber surface remained relatively rough, exhibiting low strength and toughness, poor hydrophilicity, and antistatic properties, significantly inferior to those of human hair. Compared to Example 1, these performance indicators significantly lag behind those of Example 1, failing to meet the requirements for high-quality wig materials.

[0046] Comparative Example 2 (without solvent swelling treatment)

[0047] Preparation method: Skip the solvent swelling treatment step and directly proceed to tannic acid cross-linking coating and other subsequent steps. Other parameters are the same as in Example 1.

[0048] Performance test results showed that the modified yak hair fibers had an average diameter of 74 microns, a tensile strength at break of 260 MPa, a Young's modulus of 4.7 GPa, a moisture regain of 11%, and a surface roughness of 0.55 μm. Because the keratin scale structure was not restructured by solvent swelling, the tannic acid cross-linking effect was limited, resulting in a relatively small improvement in fiber performance. Compared to Example 1, the fiber showed significant differences in strength, toughness, and hydrophilicity, demonstrating that solvent swelling treatment plays a key role in improving the properties of yak hair.

[0049] Comparative Example 3 (traditional chemical treatment method)

[0050] Preparation method: Use common chlorine oxidant to treat yak hair to improve its performance. The specific steps are: soak the yak hair in a chlorine oxidant solution of a certain concentration, treat it at a specific temperature for a certain period of time, and then perform conventional washing, neutralization, drying and other operations.

[0051] Performance test results showed that the modified yak hair fibers had an average diameter of 71 microns, a tensile strength at break of 240 MPa, a Young's modulus of 4.3 GPa, a moisture regain of 9.5%, and a surface roughness of 0.7 μm. Traditional chlorine oxidant treatment of yak hair significantly reduced its fiber strength and toughness, severely damaged its surface, and failed to effectively improve its hydrophilicity and antistatic properties. Furthermore, the treatment process caused environmental pollution, significantly inferior to the tannic acid cross-linking modification method presented in this paper.

[0052] The performance test comparison of each embodiment and comparative example is shown in Table 1 below:

[0053]

[0054] Table 1

[0055] in conclusion

[0056] 1. Mechanical Properties (Tensile Strength at Break, Young's Modulus): The bionic human hair materials of the present invention exhibited superior tensile strength and Young's modulus to the comparative examples. Examples 1 to 5 all exhibited tensile strengths exceeding 290 MPa and Young's moduli exceeding 5.0 GPa, while Comparative Examples 1 to 3 exhibited significantly lower tensile strengths and Young's moduli than the examples. This demonstrates that the present invention, through tannic acid crosslinking and modification, significantly enhances the mechanical properties of yak hair fibers, bringing them closer to the strength of human hair (human hair typically has a tensile strength of approximately 300 MPa and a Young's modulus of approximately 5 GPa).

[0057] 2. Hydrophilicity (Moisture Regain, Contact Angle): The moisture regain of the examples was above 12%, and the contact angles were below 38°. The comparative examples generally had lower moisture regains (only 9.5% for Comparative Example 3) and higher contact angles (55° for Comparative Example 3). This demonstrates that the modification method of the present invention effectively improves the hydrophilicity of yak hair, making it more conducive to maintaining cleanliness and wearing comfort.

[0058] 3. Hand feel and appearance (surface roughness, glossiness, combing resistance): The examples all had a surface roughness below 0.4 μm, a glossiness above 79%, and a combing resistance below 140 g. In contrast, the comparative examples had a higher surface roughness (0.7 μm for comparative example 3), a lower glossiness (only 55%), and a higher combing resistance (200 g for comparative example 3). This demonstrates that the bionic human hair material produced by the present invention has a smooth and delicate hand feel, a natural gloss, and closely resembles the appearance and feel of real human hair.

[0059] 4. Antistatic Performance (Electrostatic Voltage): The electrostatic voltage of the examples was below 170V, significantly lower than that of the comparative example (Comparative Example 3 reached 320V), effectively preventing hair from tangling and tangling due to static electricity. This further enhances the wearer experience and durability of the wig.

[0060] In summary, the yak hair biomimetic human hair material modified by tannic acid cross-linking in the present invention is superior to the existing technology in multiple key indicators such as mechanical properties, hydrophilicity, feel and appearance, and antistatic properties. It can effectively solve the various defects of traditional wig materials and meet the market demand for high-quality, high-performance biomimetic human hair materials.

[0061] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a yak hair biomimetic human hair material based on tannic acid cross-linking modification, characterized in that: The following steps are involved: Raw material pretreatment: Select healthy, stain-free yak hair, preferably the fine, soft hair from the yak's abdomen. Wash and degrease the hair to remove surface grease and impurities. Immerse the hair in a warm, non-ionic surfactant solution, rinse thoroughly with clean water, air dry or dry at low temperature. Bleaching is performed as needed to remove natural pigments and obtain clean, light-colored hair. Solvent swelling treatment: Immerse the pre-treated dry yak hair in hexafluoroisopropanol solvent for 0.5 to 2 hours at room temperature to allow the keratin scale structure on the fiber surface to swell and reorganize moderately, breaking some of the hydrogen bonds between keratin molecules, making the scale layer soft and rearranged. Take out the fiber and gently spin dry. Tannic acid cross-linking coating: soak the wet yak hair after HFIP treatment in a 1% to 5% tannic acid aqueous solution at room temperature for 0.5 to 2 hours. A small amount of ethanol can be added to the solution to improve permeability. Slowly shake or stir the solution during this period, and keep the solution at 40 to 60°C for gentle heating to promote the cross-linking reaction between tannic acid and keratin, forming a dense organic coating on the fiber surface. Then remove the fiber, rinse the unreacted tannic acid on the surface with clean water, and gently squeeze out the excess water. Drying, straightening and shaping: The wet fibers are straightened and hung on a stainless steel wire mesh rack or stretched on a frame. They are dried at 50-80°C for 1-2 hours until the fibers are completely dry and shaped. If necessary, the dried fibers are lightly finished to obtain yak hair bionic human hair materials with simulated human hair properties.

2. The method for preparing a yak hair biomimetic human hair material based on tannic acid cross-linking modification according to claim 1, characterized in that: In the pretreatment step, the yak hair raw material is cleaned and degreased with a non-ionic surfactant concentration of 0.1% to 0.5%, a warm water solution temperature of 30° C. to 50° C., a immersion time of 10 to 30 minutes, a rinsing number of times of not less than 3 times, and a low-temperature drying temperature of no more than 60° C.

3. The method for preparing a yak hair biomimetic human hair material based on tannic acid cross-linking modification according to claim 1, characterized in that: The bleaching treatment comprises placing the yak hair in a hydrogen peroxide solution with a mass fraction of 3% to 8%, soaking it at room temperature for 2 to 6 hours, then washing it with clean water and an acidic aqueous solution in sequence, wherein the pH value of the acidic aqueous solution is 3 to 5, the soaking time is 5 to 15 minutes, and then washing and drying.

4. The method for preparing a yak hair biomimetic human hair material based on tannic acid cross-linking modification according to claim 1, characterized in that: In the solvent swelling treatment step, the purity of the HFIP solvent is not less than 98%, and the treatment time is 1 to 1.5 hours.

5. The method for preparing a yak hair biomimetic human hair material based on tannic acid cross-linking modification according to claim 1, characterized in that: In the tannic acid cross-linking coating step, tannic acid is a natural polyphenol compound extracted from plants, the concentration of the tannic acid aqueous solution is 2% to 3%, the amount of ethanol added is 1% to 3% of the mass of the tannic acid aqueous solution, the soaking time is 1 to 1.5 hours, and the solution heating temperature is 45° C. to 55° C.

6. The method for preparing a yak hair biomimetic human hair material based on tannic acid cross-linking modification according to claim 1, characterized in that: In the drying, straightening and shaping step, the drying temperature is 60°C to 70°C, and the drying time is 1.5 to 2 hours. The post-finishing includes applying a small tension of 0.1 to 0.3 times the weight of the fiber itself to straighten it, and using a combing tool to comb it 3 to 5 times at a frequency of 50 to 100 times per minute.

7. A yak hair biomimetic human hair material based on tannic acid cross-linking modification, according to the method for preparing a yak hair biomimetic human hair material based on tannic acid cross-linking modification according to any one of claims 1 to 6, characterized in that: The bionic human hair material is composed of modified yak hair fibers, which are close to natural human hair in appearance and performance. The fiber surface is smooth and soft, with a silky luster, and has high toughness, elasticity and tensile strength. The Young's modulus is comparable to that of human hair, the hydrophilicity is improved, and the moisture regain is significantly increased compared to unmodified fibers. It exhibits excellent antistatic properties and is not easy to knot or tangle.

8. The tannic acid cross-linked modified yak hair biomimetic human hair material according to claim 7, characterized in that: The modified yak hair fiber has an average diameter of 50 to 100 microns, a tensile breaking strength of ≥300 MPa, a Young's modulus of ≥5 GPa, a moisture regain of ≥12%, and a surface roughness of ≤0.5 μm.